2015
DOI: 10.1016/j.visres.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Using the past to anticipate the future in human foraging behavior

Abstract: Humans engage in many tasks that involve gathering multiple targets from their environment (e.g. picking berries from a patch). Such foraging tasks raise questions about how observers maximize target collection—e.g. how long should one spend at one berry patch before moving to the next patch. Classic optimal foraging theories propose a simple decision rule: People move on when current intake drops below the average rate. Previous studies of foraging often assume this average is fixed and predict no strong rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 17 publications
6
19
2
Order By: Relevance
“…In the Neutral condition, the value of a target was kept constant over time. This Neutral condition is similar to previous studies on foraging (Wolfe, 2013;Zhang et al, 2015) and to studies that have shown SOS (Ashman et al, 2000;Berbaum et al, 1990). In the Decreasing condition, the value of targets decreased with each selection in a patch (i.e., the Nth+1 target was worth less than the Nth target).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the Neutral condition, the value of a target was kept constant over time. This Neutral condition is similar to previous studies on foraging (Wolfe, 2013;Zhang et al, 2015) and to studies that have shown SOS (Ashman et al, 2000;Berbaum et al, 1990). In the Decreasing condition, the value of targets decreased with each selection in a patch (i.e., the Nth+1 target was worth less than the Nth target).…”
Section: Introductionsupporting
confidence: 90%
“…Important applied tasks can also involve foraging, e.g., finding metastases in an X-ray of a cancer patient. Unlike single target search tasks, the central question is less BDid I find the target^than BWhen do I quit searching in the current display and move to the next one?R ecently, search termination on foraging tasks of humans began to attract the attention of researchers (Cain, Vul, Clark, & Mitroff, 2012;Fougnie, Cormiea, Zhang, Alvarez, & Wolfe, 2015;Hutchinson, Wilke, & Todd, 2008;Wolfe, 2013;Zhang, Gong, Fougnie, & Wolfe, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The block-wise effect is consistent with foraging theory (Stephens & Krebs, 1986) and previous empirical data both from animals (Charnov, 1976;Freidin & Kacelnik, 2011;Hayden et al, 2011;Kacelnik, 1984;McNickle & Cahill, 2009;Stephens & Krebs, 1986) and humans (Hutchinson et al, 2008;Jacobs & Hackenberg, 1996;Kolling et al, 2012;McCall, 1970;Smith & Winterhalder, 1992). The trial-wise effect is a rather direct prediction of incremental learning rules for the acceptance threshold, which have previously been proposed and studied in terms of a different class of foraging tasks, patch leaving tasks (Constantino and Daw, 2015;McNamara and Houston, 1985;Zhang et al, 2015), where choice-by-choice effects are harder to observe due to the task structure.…”
Section: Discussionmentioning
confidence: 99%
“…The eventual decision to terminate a foraging search can be affected by various factors. For example, if the searcher is looking for berries, systematic variance in patch quality (e.g., changing seasons) can significantly influence the decision to remain at a particular patch (Fougnie, Cormiea, Zhang, Alvarez, & Wolfe, 2015;Zhang, Gong, Fougnie, & Wolfe, 2015).…”
Section: Multiple-target Search or Foraging?mentioning
confidence: 99%